Digital icons : memes, martyrs and avatars - Ibrahim, Yasmin (Abingdon, Oxon ; New York, NY : Routledge, 2021)
This book offers critical perspectives on the digital iconic', exploring how the notion of the iconic is re-appropriated and re-made online, and the consequences for humanity and society. Examining cross-cultural case studies of iconic images in digital spaces, the author offers original and critical analyses, theories and perspectives on the notion of the iconic', and on its movement, re-appropriation and meaning making on digital platforms. A carefully curated selection of case studies illustrates topics such as phantom memory; martyrdom; denigration and pornographic recoding; digital games as simulacra; and memes as artification'. Situating the notion of the iconic firmly within contemporary cultures, the author takes a thematic approach to investigate the iconic as an unstable and unfinished phenomenon online as it travels through platforms temporally and spatially. The book will be an important resource for academics and students in the areas of media and communications, digital culture, cultural studies, visual communication, visual culture, journalism studies and digital humanities.
OCLC-licensed vendor bibliographic record.
Keywords: Digital media -- Philosophy; Digital media -- Social aspects; Memes; Popular culture -- Effect of technological innovations on; SOCIAL SCIENCE / Popular Culture; RELIGION / General; LANGUAGE ARTS & DISCIPLINES / Communication